We Need a New Story: Walking and the wâhkôhtowin Imagination - Donald, Dwayne (Journal of the Canadian Association for Curriculum Studies, 2021)
Inspired and guided by the nêhiyaw (Cree) wisdom concept of wâhkôhtowin, this paper frames walking as a life practice that can teach kinship relationality and help reconceptualize Indigenous-Canadian relations on more ethical terms. I argue that Indigenous-Canadian relations today continue to be heavily influenced by colonial teachings that emphasize relationship denial. A significant curricular and pedagogical challenge faced by educators in Canada today is how to facilitate the emergence of a new story that can repair inherited colonial divides and give good guidance on how Indigenous peoples and Canadians can live together differently. In my experience, the emergence of a new story can be facilitated through the life practice of walking.